Pelatihan Penggunaan Software Anatest dalam Menganalisis Butir Soal Tes Ekonomi bagi Mahasiswa Calon Guru - Ristiliana Ristiliana; Indah Wati; Yulia Novita; M. Iqbal Lubis (Anotero Lembaga Scientific Pekanbaru, 2022)
The purpose of this service is to provide information, knowledge and skills to prospective teacher students regarding the effectiveness of using Anates to validate test instruments as a support for the implementation of learning evaluation in schools. The implementation methodology is designed in the form of a simple offline training involving prospective teacher students as participants, especially final year students who are or have participated in PPL activities or are preparing their final assignments at the Faculty of Tarbiyah and Teacher Training. Bringing in resource persons who are proficient in the field of learning evaluation is carried out for 1 (one) day by providing materials related to evaluating student learning outcomes and using Anates software in order to analyze test items. The results of the community service carried out were training on using Anatest software which had been carried out for prospective teacher students of the Economics Education Study Program at the Tarbiyah and Teacher Training Faculty of UIN Suska Riau, so of the 30 participants who took part in the training it was seen that 25 students or 83% were able to operate the anatest software correctly , while 5 students still need guidance in operating the anatest software because they are still wrong in operating the anatest software. As for the ability to analyze the items, of the 30 students who attended the training, 27 students or 90% were able to analyze the items correctly and 3 students still needed further guidance.